Drought resistance and recovery in mature Bituminaria bituminosa var. albomarginata. (29th October 2014) - Foster, K.; Lambers, H.; Real, D.; Ramankutty, P.; Cawthray, G.R.; Ryan, M.H.
Abstract Few studies have investigated the response of perennial legumes to drought stress (DS) and their ability, following rewatering, to regrow and restore photosynthetic activity. We examined these responses for two genotypes of drought‐tolerant tedera (Bituminaria bituminosa var. albomarginata) and one genotype of lucerne (Medicago sativa). Plants were grown outdoors in 1‐m deep PVC pots with a reconstructed field soil profile, regularly watered for 8 months (winter to mid‐summer), and then moved to a glasshouse where either watering was maintained or drought was imposed for up to 47 days, before rewatering for 28 days. Drought stress greatly decreased shoot dry matter (DM) production in both species. Lucerne plants showed severe leaf desiccation after 21 days of withholding water. Relative leaf water content (RWC = 42%) and midday leaf water potential (LWP = −6.5 MPa) decreased in tedera in response to DS, whereas leaf angle (85°) and lateral root DM both increased. Proline and pinitol accumulated in tedera leaves during DS, and their concentration declined after rewatering. Nine days after rewatering, previously drought‐stressed tedera had similar RWC and LWP to well‐watered control plants. In tedera and lucerne, 28 days after rewatering, photosynthesis and stomatal conductance were greater than in the well‐watered controls. The lateral root DM for one tedera genotype decreased during the recovery phase but for lucerne, the lateral root DM did not change during either the drought or the recovery phases. Overall, the root systems in tedera showed greater plasticity in response to DS and rewatering than in lucerne. In conclusion, tedera and lucerne showed different physiological and morphological strategies to survive and recover from DS. Proline and soluble sugars may act as a carbon source for regrowth in tedera during recovery. In comparison with lucerne, tedera's more rapid recovery after rewatering should contribute to a greater aboveground DM yield under alternating dry and wet periods. Tedera genotypes are highly heterogeneous and selecting genotypes with enhanced concentrations of pinitol and proline could be a valuable tool to improve plant performance during DS and recovery.